KINERJA STAF/PEGAWAI SELAMA PEMBELAJARAN ONLINE TAHUN 2019-2021 - Suarga, Suarga; Dina Nurwahdaniah, Hikmah; Irmawati, Irmawati; Bahtiar, Ismatun Amriyah (Department of Islamic Education Management, 2022)
Abstract: Performance of Staff/Employees During Online Learning for the 2019-2021This study aims to determine the performance of UIN Alauddin Makassar staff. This study uses a qualitative method whose data collection techniques use primary data by distributing questionnaires to respondents containing several questions to be answered by respondents through the google form application to assess the performance of staff/employees during online learning. Based on the results of the analysis/research, it shows that most of the respondents rate the performance of the staff/employees of UIN Alauddin Makassar in the high category, namely 83% because as many as 76 people assess the performance of the staff/employees of UIN Alauddin Makassar in the high category. However, there are also respondents who rate the performance of the staff/employees of UIN Alauddin Makassar as being in the medium category with a percentage of 15% because there are 14 respondents who assess the performance of the staff/employees of UIN Alauddin Makassar in the medium category.Abstrak: Kinerja Staf/Pegawai Selama Pembelajaran Online Tahun 2019-2021Penelitian ini bertujuan untuk mengetahui kinerja staf/pegawai UIN Alauddin Makassar. Penelitian ini menggunakan metode kualitatif yang teknik pengumpulan datanya menggunakan data primer dengan menyebarkan kuesioner kepada responden yang berisi beberapa pertanyaan untuk dijawab oleh responden melalui aplikasi google form untuk menilai kinerja staf/pegawai selama pembelajaran online. Berdasarkan hasil analisis/penelitian menunjukkan sebagian besar responden menilai kinerja staf/pegawai UIN Alauddin Makassar berada pada kategori tinggi yakni 83% karena sebanyak 76 orang yang menilai kinerja staf/pegawai UIN Alauddin Makassar pada kategori tinggi. Meskipun demikian ada juga responden menilai kinerja staf/pegawai UIN Alauddin Makassar berada pada kategori sedang dengan jumlah persentase 15% karenaada 14 rang responden yang menilai kinerja staf/pegawai UIN Alauddin Makassar berada pada kategori sedang.